2021
DOI: 10.3390/polym13152492
|View full text |Cite
|
Sign up to set email alerts
|

The Low Breaking Fiber Mechanism and Its Effect on the Behavior of the Melt Flow of Injection Molded Ultra-Long Glass Fiber Reinforced Polypropylene Composites

Abstract: In this study, fiber breaking behavior, fiber orientation, length variation, and changes in melt flow ability of long glass fiber reinforced polypropylene (L-FRP) composites under different mold cavity geometry, melt fill path, and plasticization parameters were investigated. The matrix material used was polypropylene and the reinforcement fibers were 25 mm long. An ultra-long-fiber composite injection molding machine (with a three-stage plunger and injection mechanism design) was used with different mold cavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…However, as shown in Figure 10 c, the melt temperature had almost no effect on the fiber length. The result is similar to that of the previous research by Huang et al [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…However, as shown in Figure 10 c, the melt temperature had almost no effect on the fiber length. The result is similar to that of the previous research by Huang et al [ 26 ].…”
Section: Resultssupporting
confidence: 92%
“…In injection molding, the plasticizing process is affected by screw speed, processing temperature, and back pressure. Meanwhile, the injection process is determined by component geometry, injection speed, and holding pressure [23,31,32]. External factors such as contamination, processing errors, and ambient temperature also play a crucial role.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Huang, Peng, and Hwang investigated the fracture behavior and fiber length distribution of polypropylene with glass fibers during injection molding, utilizing glass fibers with a length of 25 mm. They found that increasing the screw speed contributed to the shortening of the reinforcing fibers [32]. Furthermore, Goris, Back, and Yanev studied the influence of screw speed in addition to back pressure.…”
Section: Impact Of Parameters On Fiber Length Post-injection Molding:...mentioning
confidence: 99%
“…Furthermore, research papers [3][4][5][6] investigated the influence of other process parameters, specifically pressure and temperature, on final flow length. The influence of process parameters was also investigated in publications [7][8][9]. And finally, following published papers [10][11][12] investigated various effects of process parameters, for example pressure and melt flow index, or the reason for the creation of flow marks.…”
Section: Introductionmentioning
confidence: 99%